Intelligent multi-agent system for smart microgrid energy management. (2016) - Elamine, Didi Omar; Nfaoui, El Habib; Boumhidi, Jaouad
In this paper, an intelligent energy management is presented for distributed structure such as a smart microgrid (MG) that can operate in islanded or connected mode with the main grid. To model this MG, a multi-agent is proposed. This system is based on wind power prediction and fuzzy logic control for storage device. The goal of the MAS is to control the amount of power delivered or taken from the main grid in order to reduce the cost and maximise the benefit, to achieve the mentioned goal, the neural network is proposed to predict the amount of electricity that will be produced for the next hour and fuzzy logic control for the battery to taking a reasonable decision about storing or selling electricity, finally and for the simulation, the jade platform has been used to show the impact of using the proposed system.